Data from: Loss of functional connectivity in migration networks induces population decline in migratory birds - Yanjie, Xu; Si, Yali; Wang, Yingying; Zhang, Yong; Prins, Herbert; Cao, Lei; de Boer, Willem Frederik (Zenodo, 2019)
Migratory birds rely on a habitat network along their migration routes by temporarily occupying stopover sites between breeding and non-breeding grounds. Removal or degradation of stopover sites in a network might impede movement, and thereby reduce migration success and survival. The extent to which the breakdown of migration networks, due to changes in land use, impacts the population sizes of migratory birds is poorly understood. We measured the functional connectivity of migration networks of waterfowl species that migrate over the East Asian-Australasian Flyway from 1992-2015. We analysed the relationship between changes in non-breeding population sizes and changes in functional connectivity, while taking into account other commonly-considered species traits, using a Phylogenetic Linear Mixed Model. We found that population sizes significantly declined with a reduction in the functional connectivity of migration networks; no other predictor variables were important. We conclude that the current decrease in functional connectivity, due to habitat loss and degradation in migration networks, can negatively and crucially impact population sizes of migratory birds. Our findings provide new insights into the underlying mechanisms that affect population trends of migratory birds under environmental changes. Establishment of international agreements leading to the creation of systematic conservation networks associated with migratory species' distributions and stopover sites may safeguard migratory bird populations. Population trends of the study species Species names are abbreviated: ts - tundra swan (Cygnus columbianus); sg - swan goose (Anser cygnoid); bg - bean goose (Anser fabalis); gwfg - greater white-fronted goose (Anser albifrons); lwfg - lesser white-fronted goose (Anser erythropus); glg - greylag goose (Anser anser); ct - common teal (Anas crecca); np - northern pintail (Anas acuta). yearlypop.csv Changes in functional connectivity CFC is changes in functional connectivity. The unit for the data is ...